Assessoria a grupos de catadores de materiais recicláveis : reconstruindo o problema na cooperação - William Azalim do Valle (2023)
Most waste pickers and their organizations are structured on the basis of an industrial value proposition, in which the remuneration for their work depends on an increase in the quantity of materials that are recovered and sold. In this sense, there may be an internal conflict between the environmental service of selective collection and the way it is evaluated, translated into the following image: if the increase in material consumption by the population would be harmful to the environment, it could be evaluated positively by the waste pickers, from the point of view of their remuneration. In addition to this internal conflict, by focusing exclusively on waste recovery as an institutional strategy, waste picker groups face the constraints of their subordinate position in the recycling chains. Therefore, gains in productivity and quality in the work of collecting and sorting waste do not necessarily translate into an increase in the value captured and better production conditions. If the action of waste pickers also produces positive externalities in the territory, such as socio-productive inclusion, a reduction in the use of landfills and a reduction in the extraction of virgin raw materials, then rethinking the valuation of their production becomes imperative in order to overcome the material and financial precariousness of their work. Analyzing and intervening in the economic model, in other words, in the proposal to value production in the territory, is therefore a necessity for the anthropocentric and sustainable development of these enterprises - as well as for Popular Recycling, as a societal project engendered by waste pickers. In order to better define these limits to economic reproduction and exemplify how they are faced by waste pickers and other social actors who cooperate with them, we present a reflection on the technical advisory work provided by the Alter-Nativas Production Nucleus of the Federal University of Minas Gerais to Associations and Cooperatives of Waste Pickers. By analyzing some of the interventions, we intend to reflect on the possibility of broadening the recognition of the positive effects of the actions of waste pickers in the territories, by integrating operational and institutional innovations to overcome this situation of scarcity. The question we are asking ourselves is: how can the methodological framework of advisory interventions help to overcome the financial and material precariousness experienced by waste pickers in their work?